Multi-Objective Optimization for Outer Rotor Low-Speed Permanent Magnet Motor - Guanghui Du; Chengshuai Hu; Qixun Zhou; Wentao Gao; Qizheng Zhang (Applied Sciences, 2022)
For outer rotor low-speed permanent magnet motors (LSPMMs), in the optimization design process, not only is the electromagnetic performance optimized, but the influence of the thermal load and copper loss on the temperature in the electromagnetic parameters should also be considered. However, these optimized designs that comprehensively consider electromagnetic performance and temperature characteristics are rare in the existing literature. Therefore, this paper focuses on a multi-objective optimization process considering efficiency, thermal load and copper loss. Firstly, according to the initial design, the influence of the design parameters on the efficiency and thermal load is analyzed, and the range of optimization parameters is determined. Next, the response surface is built, the response-surface analysis of electromagnetic performance is performed, and the parameter sensitivity is calculated. Then, the multi-objective optimization design is carried out by comprehensively considering the electromagnetic performance and temperature. Finally, compared with the initial scheme, the optimized scheme improves the efficiency and reduces the temperature, and the optimized scheme is verified by experimentation on a 22 kW, 56 rpm LSPMM prototype, which can provide a reference for the multi-objective optimization of LSPMMs by comprehensively considering the electromagnetic performance and temperature.